(untitled) (Revista Iberoamericana de Bioética, 2020)
The Preamble to the 2030 Agenda upholds the determination to ensure that all human beings can fulfil their potential in dignity and equality and in a healthy environment. Firstly, it discusses some ethical issues surrounding the dignity of the persons at all stages of their life. Then, since we depend on each other at some point in life, we raise the notion of interdependence as a basic relationship at the heart of the ethics of care. Finally, we maintain that the idea of interdependence alone is not enough; humanitarian solidarity is also required.